Psychometric properties and factor structure of the satisfaction with life scale in an elderly portuguese students sample. - López-Ramos, Yolanda; Navarro-Pardo, Esperanza; Fernández Muñoz, Juan José; da Silva Pocinho, Ricardo Filipe (Anales de Psicología / Annals of Psychology, 2017)
The main purpose of this study is to analyze the psychometric properties of the Satisfaction With Life Scale (SWLS) in a 363 retirees students sample from several Portuguese universities. The 70% were female (253) and 30% were male (110) with an average age of 67 years (SD = 7.59) and a range from 48 to 90 years. R commander was used for Exploratory Factor Analysis (EFA) and Amos 18.0 module for Confirmatory Factor Analysis (CFA). One factor solution was the best-fitting model. The internal consistency of the SWLS was .769. Correlational analysis showed negative relationships with loneliness (UCLA Scale) and symptoms of depression (15-GDS), supporting concurrent validity. The SWLS can be used with confidence in future research among elderly students to measure their life satisfaction. Some limitations of the results and its applications in other samples are discussed.